2015
DOI: 10.1016/j.entcs.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Proving Concurrent Constraint Programming Correct, Revisited

Abstract: Concurrent Constraint Programming (CCP) is a simple and powerful model of concurrency where processes interact by telling and asking constraints into a global store of partial information. Since its inception, CCP has been endowed with declarative semantics where processes are interpreted as formulas in a given logic. This allows for the use of logical machinery to reason about the behavior of programs and to prove properties in a declarative way. Nevertheless, the logical characterization of CCP programs exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In [32,33] we have shown that CCP can indeed be used as a declarative language to implement simulation tools for biochemical systems. Such tools can be improved by the recent findings in [34], where optimizations for CCP were derived from the proof theory of linear logic. Similarly, we hope that the results in this paper and the body of knowledge in proof theory will allow us to build more automatic (and efficient) theorem provers to verify biochemical systems.…”
Section: Model Checking Theorem Proving and Concurrency Theorymentioning
confidence: 99%
“…In [32,33] we have shown that CCP can indeed be used as a declarative language to implement simulation tools for biochemical systems. Such tools can be improved by the recent findings in [34], where optimizations for CCP were derived from the proof theory of linear logic. Similarly, we hope that the results in this paper and the body of knowledge in proof theory will allow us to build more automatic (and efficient) theorem provers to verify biochemical systems.…”
Section: Model Checking Theorem Proving and Concurrency Theorymentioning
confidence: 99%